Flunarizine Induced Parkinsonism in Migraine Group: A Nationwide Population-Based Study - Lin, Wei; Lin, Cheng-Li; Hsu, Chung Y.; Wei, Cheng-Yu (Frontiers in Pharmacology, 2019)
Background: Flunarizine (Fz) is a first-line prophylactic medication that is widely used in migraine. However, Fz has been recognized as a potential cause of drug-induced parkinsonism for a long time. However, to our knowledge, there has been no population-based subgroup analyses for Fz-induced parkinsonism (FIP) in migraine patients. Methods: Data were obtained from the Taiwan’s National Health Insurance Research Database. The study comprised 6,470 migraine patients who were divided into two groups, based on their exposure or non-exposure to Fz. Results: During the study period (2000–2012), the incidence rate of parkinsonism was 1.92% and 8.72% in the control and Fz -treated groups, respectively. In the study population, the adjusted hazard ratio was 4.07 (95% confidence interval CI: 2.84–5.85). In 45–64-year old subjects and  65-year old subjects, the risk of FIP was 3.18 times (95% CI = 1.63–6.20) and 4.89 times (95% CI = 3.09–7.72) more than that in the controls. The Fz-treated subjects with comorbidities also had a higher risk (4.54, 95% CI: 3.14-6.57). An average annual cumulative Fz dose > 445 mg was accompanied by the greatest risk of FIP; Fz use for > 60 days is a cut-off point for predicting future FIP. Conclusion: At the population level, this study showed a complete picture of FIP in migraine patients. FIP is associated with older age, history of comorbidities, exposure to high-dose of Fz, and longer duration of exposure to Fz.